Making Space for Indigenous Approaches in the Southwest Pacific? The Spatial Politics of Peace Scholarship and Practice. Issue 5 (20th October 2022) - Brigg, Morgan; George, Nicole; Higgins, Kate
ABSTRACT: Indigenous approaches to space and place in the Southwest Pacific are crucial to governing peace. However, 'making space' for these approaches can only be progressed if scholars and practitioners recognize their emplacement within hegemonic systems of knowledge and the contested entanglement of Indigenous and introduced systems in peacebuilding practice. Addressing this challenge requires respectful and careful engagement with diverse peoples and colonially inflected peacebuilding practice, attending to the emplacement of peace and conflict scholarship amidst the colonial politics of knowledge, and critical reflection on the ways that peacebuilding expertize is defined, attributed and evaluated.